Who are we, and what is the nature of reality? Insights from scientists’ spiritually transformative experiences - Tressoldi, Patrizio E. (Journal for the Study of Spirituality, 2023)
To analyze the first-person phenomenological Spiritually Transformative Experiences (STEs) of a sample of scientists and academics, the first-person phenomenological accounts of 40 scientists’ and/or academics’ Spiritually Transformative Experiences were analyzed with respect to their perceived changes in the nature of the personal self and the nature of reality. Eighty-five percent of experiencers described a dissolution of the boundaries of their personal self; this was experienced by 62.5% as a sense of boundless oneness, with the characteristics of pure unconditional love (45%). As to the nature of reality, 60% also experienced reality as unitive, and 47.5% of the experiencers described its essence as unconditional love, bliss, and luminosity (27.5%), with some describing it as filled with energy, intelligence and beyond time. For all individuals, the experiences were considered truly real. For those who have not had similar experiences, their ontological status remains an empirical question.